Parents' and Children's Gender: the effect of parental expectations in children's performance - Prieto-Latorre, Claudia; Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro (My University, 2018)
Parental expectations have been found in the literature to explain their children’s academic achievement. Nevertheless, most of the evidence on this issue is the result of the endogeneity of parental expectations when explaining students’ performance. In this context, we propose to solve this issue by using longitudinal data for the education period of the transition between primary and secondary education, employing time fixed effects to analyse the effect of parental expectations on students’ progression – being the latter measured by students’ academic achievement and their likelihood of grade repetition. We go more into depth on this issue by the study of gender differences of this effect, using all possible combinations between parents’ and children’s genders. Our results have shown that higher fathers’ and mothers’ expectations improve students’ progression, but parents seem to be more demanding with girls in terms of levels of education.
Keywords: Rendimiento académico; Gender; Expectations; Grade retention